Analysis of Dll4 regulation reveals a combinatorial role for Sox and Notch in arterial development. - Sacilotto, N; Monteiro, R; Fritzsche, M; Becker, P; Sanchez-Del-Campo, L; Liu, K; Pinheiro, P; Ratnayaka, I; Davies, B; Goding, C; Patient, R; Bou-Gharios, G; et al. (2013)
The mechanisms by which arterial fate is established and maintained are not clearly understood. Although a number of signaling pathways and transcriptional regulators have been implicated in arterio-venous differentiation, none are essential for arterial formation, and the manner in which widely expressed factors may achieve arterial-specific gene regulation is unclear. Using both mouse and zebrafish models, we demonstrate here that arterial specification is regulated combinatorially by Notch signaling and SoxF transcription factors, via direct transcriptional gene activation. Through the identification and characterization of two arterial endothelial cell-specific gene enhancers for the Notch ligand Delta-like ligand 4 (Dll4), we show that arterial Dll4 expression requires the direct binding of both the RBPJ/Notch intracellular domain and SOXF transcription factors. Specific combinatorial, but not individual, loss of SOXF and RBPJ DNA binding ablates all Dll4 enhancer-transgene expression despite the presence of multiple functional ETS binding sites, as does knockdown of sox7;sox18 in combination with loss of Notch signaling. Furthermore, triple knockdown of sox7, sox18 and rbpj also results in ablation of endogenous dll4 expression. Fascinatingly, this combinatorial ablation leads to a loss of arterial markers and the absence of a detectable dorsal aorta, demonstrating the essential roles of SoxF and Notch, together, in the acquisition of arterial identity.